Using the method of principal components in study of the data obtained by means of X-ray fluorescent spectral analysis on the elemental composition of clothing damages areas at the shooting of nonlethal elastic bullets "Teren-12P" ammunition - Sapielkin, Victor (Journal of Education, Health and Sport, 2019)
This work is executed in accordance with individual subjects "Medico-legal diagnostics of the damages caused at shots by elastic bullets from the smooth-bore weapon of 12th caliber", state registrations number #0111U002178, that is executed on the department of forensic medical examination in KhMAPGA. The definition of scientific-based criteria for objectively diagnoses of cloth damages caused at shots by the “Teren-12P” cartridges elastic bullets, which are in service with the law enforcement agencies of Ukraine, is currently a topical problem in forensic medicine. Using six common samples of clothing fabrics and ballistic plasticine, experimental shots from the “Fort-500A” pump gun were carried out with “Teren-12P” cartridges bullets at distances of 0-15 m. Using X-ray fluorescent spectral analysis (XRF) the elemental composition of bullets, powder gases removed from the gun barrel after the shot, as well as the target fabric before the shots and in the damage areas after the shots were determined. Analysis and processing of the qualitative and quantitative composition of chemical elements in the damage areas was carried out using the chemometric approach – the method of main components. The main criteria for diagnosing cloth damage by the “Teren-12P” cartridge bullet with the help of XRF, which can be used in the relevant expert studies, are established.